FINANCIAL PERFORMANCE OF BANKING SECTOR BEFORE AND AFTER IMPLEMENTATION OF IFRS-BASED PSAK - Zahara, Rizka Verina; Chariri, Anis (Diponegoro Journal of Accounting, 2024)
This research aims to investigate the differences in the financial performance (CAR, NPL, ROA, BOPO, and LDR) of the banking industry before and after the implementation of IFRS-based PSAK in the 2011, 2013, and 2022. This study proposes the hypothesis that there is an increase in the variables between financial statements prepared by IFRS-based PSAK and financial statements prepared by Indonesian accounting standards. The population of this research is banking companies listed by the Financial Services Authority of Indonesia in 2011, 2013, and 2022. The sampling method used is purposive sampling. The Paired sample t-test is used to test the hypothesis. The findings show increases in CAR, ROA, BOPO, and LDR after implementing IFRS-based PSAK.